Day-of-The-Week Anomaly on Different Stock Capitalization: Evidence from Indonesian Stock Market - Dadang Wahyu Juniarwoko; Tony Irawan; Lukytawati Anggraeni (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The aim of this study is to determine whether the “Day-of-The-Week Anomaly” (DOWA) exists on different stock capitalization in Indonesian stock market. A total of 58 stocks listed in both LQ45 index and Pefindo25 index used to represent large cap stocks and small and medium cap stocks respectively. The Ordinary Least Squares (OLS) method and ARCH/GARCH model were employed to capture the DOWA and the daily volatility behavior for the period between January 2010 and December 2015. The result reveals that DOWA exist for a significant proportion of individual stocks in both LQ45 and Pefindo25. Monday was found to have the lowest mean returns while Wednesday has the highest mean return. The differences between Monday’s return and return of the other days ranged from 0.15 to 0.41 percent. LQ45 stocks also found to have slightly higher Wednesday’s volatility than of Pefindo25 stocks. It indicates that the higher return of the LQ45 is naturally accompanied by a higher risk.JEL Classification: G02, G10, G17Keywords: Day-of-The-Week Anomaly, Indonesia, LQ45, Pefindo25, Stock Market